Penerapan Media Video Animasi dan Powerpoint Terhadap Minat dan Hasil Belajar Siswa dengan Model Pembelajaran Problem Based Learning (PBL) pada Materi Kimia Kelas XI Sekolah Chandra Kumala - Muhammad Azwir Azandi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study evaluates the impact of animation video and Powerpoint media on students' interest and learning outcomes in chemistry for class XI at Chandra Kumala School, utilizing the Problem Based Learning (PBL) model. The results show that the average pretest score for the experimental class 1 using animation videos increased from 49.25 to 85.75, with a significant improvement (t-value of 7.214, p < 0.05, N-Gain of 0.719). In contrast, experimental class 2 using Powerpoint had a pretest average of 63.75 and a posttest average of 73.75 (N-Gain of 0.275). The overall results indicate that class 1 performed better, with a significant difference in learning outcomes between the two classes (t-value of 3.650, p < 0.05). This study concludes that animation video media is more effective than Powerpoint in enhancing students' chemistry learning outcomes, despite some technical and linguistic challenges faced during implementation.